Efeito do TNF-α na atividade funcional de fagócitos do colostro humano de mães com excesso de peso - Gadenz, Gabriella Regina Borges (2021)
Maternal obesity has concerned scientists because of the maternal and fetal impacts of chronic lowgrade inflammation caused by excess adipose tissue in the body. This chronic inflammation directly influences pregnancy through the passage of inflammatory mediators via the placenta, resulting in alterations in embryonic and fetal development, and also in the postpartum period, through the alteration of the bioactive components of colostrum and breast milk, which can have important effects on the newborn's defense against various pathogenic microorganisms. Therefore, the aim of this work was to evaluate the modulation by the cytokine TNF-α of the functional activity of human colostrum phagocytes from overweight nursing mothers to EPEC. For this, colostrum samples were collected from mothers who were overweight and obese pregestationally and without any other previous comorbidity or infection. These samples were centrifuged to obtain the isolated mononuclear cells. These cells were incubated with TNF-α and with EPEC to evaluate the analysis of cell viability, phagocytosis index, microbicidal index and intracellular calcium release by colostrum phagocytes. The cell viability analysis was higher than 89% in all nutritional states. The mononuclear cells were able to phagocytize EPEC even without stimulus, but when incubated with TNF-α, this rate increased considerably. As for the microbicidal index, stimulation with TNF-α was shown to facilitate the death of the bacteria in the obesity group. The analysis of intracellular calcium release did not show statistical differences between the groups and treatment. This suggests that the phagocytosis process in this study model is not dependent on intracellular calcium, and may depend on other mechanisms or surface receptors. It is possible to conclude that, TNF-α presents itself as a possible modulator of human colostrum MN cells, facilitating phagocytosis in the overweight mothers group and improving the microbicidal response in the obese group, and may become a possible alternative treatment in the future, improving the immune response and protecting the newborn through breastfeeding.